2011
DOI: 10.1186/2040-2392-2-11
|View full text |Cite
|
Sign up to set email alerts
|

Transient and steady-state auditory gamma-band responses in first-degree relatives of people with autism spectrum disorder

Abstract: BackgroundStimulus-related γ-band oscillations, which may be related to perceptual binding, are reduced in people with autism spectrum disorders (ASD). The purpose of this study was to examine auditory transient and steady-state γ-band findings in first-degree relatives of people with ASD to assess the potential familiality of these findings in ASD.MethodsMagnetoencephalography (MEG) recordings in 21 parents who had a child with an autism spectrum disorder (pASD) and 20 healthy adult control subjects (HC) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
138
4
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(157 citation statements)
references
References 82 publications
(93 reference statements)
9
138
4
1
Order By: Relevance
“…Across visual and auditory paradigms the variations in GBA power effects (hypo-or hyperactivity) in ASD can be reconciled with the more consistent reports of reduced phaselocking in ASD and ASD-related populations where this was also assessed, noting that reduced phase-locking will be associated with an imbalance between evoked and induced power (Rojas et al, 2011 Delay in M100 evoked response; reduced gamma-band evoked activity at both time points Table 2: A summary of key electrophysiological studies into auditory processing in ASD.…”
Section: Task-related Gba In Asd: Visual and Auditory Processingmentioning
confidence: 82%
“…Across visual and auditory paradigms the variations in GBA power effects (hypo-or hyperactivity) in ASD can be reconciled with the more consistent reports of reduced phaselocking in ASD and ASD-related populations where this was also assessed, noting that reduced phase-locking will be associated with an imbalance between evoked and induced power (Rojas et al, 2011 Delay in M100 evoked response; reduced gamma-band evoked activity at both time points Table 2: A summary of key electrophysiological studies into auditory processing in ASD.…”
Section: Task-related Gba In Asd: Visual and Auditory Processingmentioning
confidence: 82%
“…Rojas et al (2011) took MEG recordings of 21 parents of autistic probands and 21 adult controls reporting a reduction in steady-state gamma-band responses in the autism-parent group, similar to the responses of children diagnosed with autism (e.g. Wilson et al 2007).…”
Section: Meg Studies and The Bapmentioning
confidence: 98%
“…DTI, ERP and MEG studies of autistic probands and their relatives are also starting to provide further useful ways of exploring the neurodevelopmental pathways leading to autism by better understanding its biological liability (e.g. Elsabbagh et al 2009a;Rojas et al 2011).…”
Section: Summary Of Findings and Future Directionsmentioning
confidence: 99%
“…In the auditory domain, reduced entrainment to auditory stimulation at 40 Hz in participants with ASD (Wilson et al, 2007) as well as their firstdegree relatives (Rojas et al, 2011) has been demonstrated. In contrast, during visual perception there is evidence for both hyperactivity and hypoactivity of gamma-band oscillations (Grice et al, 2001;Brown et al, 2005;Milne et al, 2009;Isler et al, 2010;Stroganova et al, 2012), raising the question of the link between high-frequency oscillations and perceptual dysfunctions in the disorder.…”
Section: Introductionmentioning
confidence: 99%